2020
DOI: 10.3390/ijms21041347
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Fraction of Aqueous Extract of Lentinula edodes Inhibits Osteoclastogenesis by Suppressing NFATc1 Expression

Abstract: Bone tissue is continuously remodeled by the coordinated action of osteoclasts and osteoblasts. Nuclear factor-activated T cells c1 (NFATc1) is a well-known transcription factor for osteoclastogenesis and transcriptionally activated by the c-Fos and nuclear factor-kappa B (NF-κB) signaling pathways in response to receptor activation of NF-κB ligand (RANKL). Since excessive RANKL signaling causes an increase of osteoclast formation and bone resorption, inhibition of RANKL or its signaling pathway is an attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Osteoclast precursor (OCP) cells were generated as described previously [ 18 ]. Briefly, bone marrow cells were isolated from 6–7-week-old ICR male mouse with α-minimum essential medium (α-MEM) supplemented with 10% FBS and M-CSF (5 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Osteoclast precursor (OCP) cells were generated as described previously [ 18 ]. Briefly, bone marrow cells were isolated from 6–7-week-old ICR male mouse with α-minimum essential medium (α-MEM) supplemented with 10% FBS and M-CSF (5 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…mRNA-Seq reads were aligned to reference mouse genome (mm10 assembly) using TopHat. HOMER program was used to analyze RNA-seq data performed as described [ 18 ]. The cut-off parameters were set at fold change ≥ 2 and FDR < 0.05 (Benjamin-Hochberg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in case of GSE142866 in Table 3 4. Overall, total 16 CPs, 8 CPs for OCU and 8 CPs for OCD, were produced from the 11 studies including GSE111237 [33], GSE142866 [34], GSE149887 [35], GSE152986 [36], GSE17563 [1], GSE20850 [37], GSE30160 , GSE37219 [38], GSE57468 [39], GSE76988 [40], GSE72846 [41] and GSE135479 [42]. As noticeable, some studies include both OCU and OCD cases and some only one type.…”
Section: Choosing Appropriate Geo Data Setsmentioning
confidence: 99%
“…Other phenolic compounds, such as tanshinol ( Luo S. et al, 2016 ) and salvianolic acid B ( Luo S. Y. et al, 2016 ), were shown to have bone anabolic properties, and hydroxysafflor yellow A was found to have both bone anabolic and anti-resorptive properties ( Liu L. et al, 2018 ). The ability of alkaloids such as evodiamine ( Yin et al, 2019 ) to trigger bone remodeling and the capacity of fungal extracts—e.g., from shiitake mushroom ( Lee H. et al, 2020 ) and from Penicillium velutinum ( Chen et al, 2018 )—to successfully rescue OP phenotype was successfully demonstrated in the zebrafish GIOP model. Osteoactivity of the TMC formulations Xian-ling-gu-bao ( Wu et al, 2017 ) and Zuogui pill ( Yin et al, 2018 ), commonly used in Asiatic countries to treat primary OP, was also addressed in the zebrafish GIOP model, unveiling their potential to also counteract secondary forms of OP.…”
Section: Applicationsmentioning
confidence: 99%